2570. HCV Screening Practices Among Adolescents and Young Adults in a National Sample of Federally Qualified Health Centers in the United States. (26th November 2018) - Epstein, Rachel L; Wang, Jianing; Mayer, Kenneth; Puro, Jon; Horsburgh, C Robert; Linas, Benjamin P; Assoumou, Sabrina A
Abstract: Background: The opioid crisis has been associated with an increase in hepatitis C virus (HCV) infections among 15–30 year olds. Federally Qualified Health Centers (FQHCs) provide comprehensive healthcare to diverse and underserved communities. However, little is known about HCV screening practices among adolescents and young adults seen at FQHCs across the United States. Objective. To characterize the continuum of HCV testing and care among adolescents and emerging adults in a large national sample of US FQHCs. Methods: We used the OCHIN electronic medical record to create a retrospective cohort of 13 to 21 year olds who had a least 1 outpatient visit at any of 98 participating US FQHCs across 19 states from 2012 to 2017. Primary outcome was HCV testing during this timeframe. We also identified predictors of HCV screening using multivariable logistic regression adjusting for age, sex, race/ethnicity, and substance use. Results: Among 269, 287 youth who met inclusion criteria, 54.7% were female, 37.6% White, 33.5% Hispanic, 17.6% Black, and 11.3% other. Mean [SD] age at first HCV screening was 18.5 [2.2] years. Over the study period, 2.5% (6849/269, 287) were tested for HCV and 153 (2.2%) had reactive HCV testing. Of those, 117 (76.5%) had confirmatory RNA testing and 65 (55.6%) had detectable RNA. Thirty-five percent (325/933) with ICD-9 codes for opioid-use disorder (OUD) and 8.9% (2080/23, 345) with any ICD-9 code for drug use were tested for HCV. Only 10.6% (728/6, 849) of individuals tested for HCV had also been tested for human immunodeficiency virus (HIV). Older age (19–21 vs. 13–15 years old at study end, aOR 5.64, 95% CI 5.13–6.19), Black race (aOR 1.88, 95% CI 1.76–2.00), and ICD-9 codes for substance-use disorder, in particular amphetamine (aOR 5.82, 5.10–6.64), opioids (aOR 3.50, 2.92–4.19), cocaine (aOR 2.90, 2.43–3.47), or cannabis (aOR 2.46, 2.31–2.62) were independently associated with HCV testing in multivariable analysis. Conclusion: During the current opioid crisis, only a third of adolescents/young adults diagnosed with OUD in a large national sample of FQHCs were tested for HCV. In addition, only 10% of those tested for HCV were also screened for HIV. Initiatives are needed to increase HCV and HIV screening among at-risk youth at FQHCs. Disclosures: All authors: No reported disclosures.